Pathogenicity of and plant immunity to soft rot pectobacteria - Davidsson, Pär R.; Kariola, Tarja; Niemi, Outi; Palva, Tapio (Frontiers in Plant Science, 2013)
Soft rot Pectobacteria are broad host range enterobacterial pathogens that cause disease on a variety of plant species including the major crop potato. Pectobacteria are aggressive necrotrophs that harbor a large arsenal of plant cell wall degrading enzymes as their primary virulence determinants. These enzymes together with additional virulence factors are employed to macerate the host tissue and promote host cell death to provide nutrients for the pathogens. In contrast to (hemi)biotrophs such as Pseudomonas, type three secretion systems (T3SS) and T3 effectors do not appear central to pathogenesis of Pectobacteria. Indeed, recent genomic analysis of several Pectobacterium species including the emerging pathogen Pectobacterium wasabiae has shown that many strains lack the entire T3SS as well as the T3 effectors. Instead, this analysis has indicated the presence of novel virulence determinants. Resistance to broad host range Pectobacteria is complex and does not appear to involve single resistance genes. Instead, activation of plant innate immunity systems including both SA and JA/ET mediated defenses appears to play a central role in attenuation of Pectobacterium virulence. These defenses are triggered by detection of pathogen-associated molecular patterns (PAMPs) or recognition of modified-self such as damage-associated molecular patterns (DAMPs) and result in enhancement of basal immunity (Pattern-triggered immunity, PTI). In particular plant cell-wall fragments released by the action of the degradative enzymes secreted by Pectobacteria are major players in enhanced immunity towards these pathogens. Most notably bacterial pectin degrading enzymes release oligogalacturonide (OG) fragments recognized as DAMPs activating innate immune responses. Recent progress in understanding OG recognition and signaling allows novel genetic screens for OG-insensitive mutants and will provide new insights into plant defense strategies against necrotrophs such as Pectobacteria.